2020
DOI: 10.4491/eer.2020.241
|View full text |Cite
|
Sign up to set email alerts
|

Removal of fluoride from an aqueous solution by batch and column process using activated carbon derived from iron infused Pisum sativum peel: characterization, Isotherm, kinetics study

Abstract: The present study investigated the adsorption efficiency of magnetic activated carbon was synthesized by waste biomass of Pisum sativum (peel) and pyrolysis at 500˚C temperature (MPPAC-500). Derived activated carbon was applied for removal of fluoride from aqueous solution. The MPPAC-500 was characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), zeta potential, X-ray Diffraction (XRD) and Particle Size Analyser. The fluoride sequestration study was performed in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The negative values of the free enthalpy ΔG° indicate that the adsorption of fluoride ions on the modified zeolite is a spontaneous process [ 17 , 54 , 55 ]. The decrease of ΔG° with increasing temperature is another parameter that indicates the adsorption takes place without additional outputs.…”
Section: Resultsmentioning
confidence: 99%
“…The negative values of the free enthalpy ΔG° indicate that the adsorption of fluoride ions on the modified zeolite is a spontaneous process [ 17 , 54 , 55 ]. The decrease of ΔG° with increasing temperature is another parameter that indicates the adsorption takes place without additional outputs.…”
Section: Resultsmentioning
confidence: 99%
“…To face the threat of As (III) and As (V), Sahu et al suggested the use of magnetized carbon-based adsorbents with AC derived from pea peels [60]. The activation was physically carried out by pyrolysis at 500 • C (MPAC-500) and 600 • C (MPAC-600), with the latter having the better results.…”
Section: Pea Peel Acmentioning
confidence: 99%
“…Pea Peel AC Sahu et al examined the removal of fluoride from an aqueous solution by both batch and column experiments with activated carbon derived from pea peels, activated by FeCl 3 and pyrolysis[60]. The efficiency of MPPAC-500 was evaluated by the study of the effects of temperature, kinetics, and pH, and the material was characterized.…”
mentioning
confidence: 99%
“…Sahu et al [164] evaluated the fluoride adsorption with a magnetic AC prepared using pea peel biomass impregnated with FeCl 3 and pyrolyzed at 500 °C. Fluoride removal tests were performed with column and agitated tank modes.…”
Section: Use Of Magnetic Adsorbents For Water Pollutant(s) Removalmentioning
confidence: 99%